The influence of the Fourth Industrial Revolution on organisational culture: An empirical investigation - Singaram, Shwetha; Mayer, Claude-Hélène (Frontiers in Psychology, 2022)
The Fourth Industrial Revolution (4IR) is known to transform and create opportunities for the world of work. However, little is known about how the future workforce, such as university students, are being equipped and exposed to 4IR technologies and ways of thinking in a South African (SA) context. This study’s findings contribute to understanding the influence of organisational culture on the uptake of 4IR technology within higher education (HE) in SA during a pandemic. The study uses Edgar Schein’s theoretical framework to explore the organisational culture at a university in the Gauteng province. The article responds further to the questions on how 4IR technology and principles are understood and applied within the context, and how to investigate to what extent the 4IR is reflected upon or embedded in the university’s culture. A qualitative research design is used, and data are gathered through in-depth, semi-structured interviews from seven purposively selected academic and senior management staff members. Thematic analysis uncovered that the university’s ambitious and competitive culture contributed to a positive uptake of 4IR technology and principles, even pre-COVID-19. Furthermore, the specific influence of the university’s Vice-Chancellor to build 4IR thinking into the university helped shape more 4IR thinking and technologies, such as artificial intelligence, whilst still considering the existing disparities of SA, as a developing country.